Problems & solutions in group theory for physicists - Ma, Zhongqi, 1940- (World Scientific, 2004)
"This book is aimed at graduate students in physics who are studying group theory and its application to physics. It contains a short explanation of the fundamental knowledge and method, and the fundamental exercises for the method, as well as some important conclusions in group theory." "The book can be used by graduate students and young researchers in physics, especially theoretical physics. It is also suitable for some graduate students in theoretical chemistry."--Jacket.